Antioxidant and antimicrobial activities of Callistemon comboynensis essential oil - Abdelhady, Mohamed I.; Aly, Hamdy A. H. (Free Radicals and Antioxidants)
Introduction: The genus Callistemon is known in folk medicine for its anticough, antibronchitis, and insecticidal effects and its volatile oils have been used as antimicrobial and antifungal agents. Methods: The essential oils obtained by hydrodistillation of the leaves of Callistemon comboynensis (Cc) was investigated by GC/MS. Antioxidant activity of Cc was investigated using 1,1-diphenyl-2-picrylhydrazyl (DPPH). The antimicrobial activity of the essential oil of Cc was evaluated against both gram positive (Bacillus subtilis and Staphylococcus aureus), gram negative (Proteus vulgaris, Pseudomonas aeruginosa) and a pathogenic fungus Candida albicans. Results: It was found that Cc afford 0.22% volatile oil. The major components of the volatile oil of Cc are 1, 8-cineol (53.03%), eugenol (12.1%), methyl eugenol (9.2%) and α-pinene (8.3%). The oil had pronounced antibacterial and antifungal activities on all the tested microbes. Nevertheless, Cc leaf oil extract exhibited high antioxidant activity (91.1 ± 0.3 %) at a concentration of 1000 µg.ml-1, comparable to 100 µg.ml-1 gallic acid (95.7 ± 2).
Keywords: C. comboynensis; essential oil; cineole; antioxidant; and antimicrobial activity